PENGARUH SELF EFFICACY, ORGANIZATIONAL JUSTICE, DAN PERCEIVED ORGANIZATIONAL SUPPORT TERHADAP ORGANIZATIONAL CITIZENSHIP BEHAVIOR PADA KARYAWAN PERUSAHAAN UNO.CO - Azahra Salsabila (2023)
This research's purpose is to determine and prove the influence of self-efficacy, organizational justice, and perceived organizational support on organizational citizenship behavior. This research analyze 55 staff of the Uno.Co company as a sample, with a sampling technique using a saturated sample. The SEM based PLS is chosen as data analysis technique in this study. The results of the study shows that (1) self-efficacy has a positive effect on organizational citizenship behavior, (2) organizational justice has a positive effect on organizational citizenship behavior, (3) perceived organizational support has a positive effect on organizational citizenship behavior, (4) self efficacy, organizational justice, and perceived organizational support simultaneously have a positive effect on organizational citizenship behavior. Keywords: self efficacy, organizational justice, perceived organizational support, organizational citizenship behavior